Intra cranial complications of tuberculous otitis media - M Prakash; J Carlton Johnny (Wolters Kluwer Medknow Publications, 2015)
Tuberculosis is one of the most common infections in the world. It is seen that tuberculous otitis media (TOM) is almost secondary to pulmonary tuberculosis. In this review we have tried to deal with all the aspects of the intra cranial complications of TOM such as tuberculoma, otitic hydrocephalus, brain abscess and tuberculous meningitis. The aspects covered in this review are the pathology, clinical features, and investigations of the intra cranial manifestations.